Landscaping in Florida with Fire in Mind - Martha monroe; Raelene Crandall; Jennifer Fill; Alan Long (EDIS)
Wildfire risk depends on the landscape surrounding communities and the vegetation immediately surrounding homes. To protect their homes, residents should consider both the materials used to construct their houses and the vegetation type and arrangement in the area around them. This publication presents information on how to landscape the vegetation, selecting plants with low flammability, pruning ladder fuels, and removing highly combustible materials to create a low-risk area of defensible space around their houses.